Barriers and Facilitators of the Outpatient Health Service Use by the Elderly - Neda Soleimanvandi Azar; Seyed Hossein Mohaqeqi Kamal; Homeira Sajadi; Gholam Reza Ghaedamini Harouni; Salaheddin Karimi; Ameneh Setareh Foroozan (University of Social Welfare & Rehabilitation Sciences, 2020)
Objectives:  Increasing care needs for the elderly are an important concern for different countries, especially those with an aging population. It is important for health policy making to have knowledge of the factors affecting the use of health services in the elderly to identify the potential problems and develop appropriate interventions for improving utilization and increasing access to health services. This study aims to investigate the barriers and facilitators of the outpatient health service use in the elderly Methods & Materials: In this systematic review, studies in English published from 1996 to 2019 were searched in Web of Science, PubMed and Scopus databases using PRISMA guidelines and related keywords. After eliminating duplicate and irrelevant articles, the quality of remaining articles was evaluated by two evaluators independently, based on STROBE checklist. Narrative synthesis method was used to combine the data Results: Forty-four eligible studies were included for the review. The determinants of the health service use were divided into three categories of predisposing factors (e.g. age, gender, marital status, ethnicity), enabling factors (e.g. income, insurance coverage, education level, employment status, social network, social support), and need factors (e.g. having chronic disease, self-assessed health status, severity of disease, number of diseases, comorbid diseases, physical disability, unhealthy lifestyle). Findings showed that age >80 years, ethnic minority, being unemployed and retired, low educational level, small and limited social network, and physical disability were the barriers to using outpatient health services, while being female, married, having insurance, social support, having a companion during a disease, having children, high income level, and shorter distance to the health care centers were the facilitators of using outpatient health services in the elderly Conclusion: A group of factors are associated with the outpatient health service use by the elderly. These factors include predisposing, enabling, and need-related factors according to Andersen's behavioral model of health service use. Interventions to increase the use of health services by the elderly should be based on these factors, and should be taken into account by the policymakers to reduce the burden of health services caused by diseases.